9(x-2)=-12(2x-4)

Simple and best practice solution for 9(x-2)=-12(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)=-12(2x-4) equation:


Simplifying
9(x + -2) = -12(2x + -4)

Reorder the terms:
9(-2 + x) = -12(2x + -4)
(-2 * 9 + x * 9) = -12(2x + -4)
(-18 + 9x) = -12(2x + -4)

Reorder the terms:
-18 + 9x = -12(-4 + 2x)
-18 + 9x = (-4 * -12 + 2x * -12)
-18 + 9x = (48 + -24x)

Solving
-18 + 9x = 48 + -24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24x' to each side of the equation.
-18 + 9x + 24x = 48 + -24x + 24x

Combine like terms: 9x + 24x = 33x
-18 + 33x = 48 + -24x + 24x

Combine like terms: -24x + 24x = 0
-18 + 33x = 48 + 0
-18 + 33x = 48

Add '18' to each side of the equation.
-18 + 18 + 33x = 48 + 18

Combine like terms: -18 + 18 = 0
0 + 33x = 48 + 18
33x = 48 + 18

Combine like terms: 48 + 18 = 66
33x = 66

Divide each side by '33'.
x = 2

Simplifying
x = 2

See similar equations:

| a^2-10a-ay+10y= | | t^2-17t+6=0 | | t^2-17y+6=0 | | 2y+1=5y-5 | | 21x^2+47x+20=0 | | 45x^3+123x^2+42x=0 | | 12(2x-3)=4(6x+5) | | -5=4(x+4)-3x | | w^2-d^2= | | 3(x-1)=-4x+36 | | (x)2+7x+12=0 | | 8x^2+48x-56= | | 1(x+2)+33=-4x | | (1/4)(3x+27)=3x | | (1/3)(3x-36)=5x | | r^3-6r^2-36r+216= | | -a-6=9 | | 35+12x+x^2=0 | | a^2-12ab+32b^2=0 | | v^3+22v^2+121v= | | -4x+7=19 | | 5x^2+22x+8= | | 8(4x-1)=24x | | 6(x-2)=3x+6 | | r^2+25-10r= | | 16+-24x+9x^2=0 | | (5x-1)(5x-1)=7 | | 9x^2=24x-16 | | (1/4)(2x+6)=4x | | 38=(x+3)+(x+9)+(x^2-2x)+(3x-2) | | x(7x+22)+16=0 | | 2x^2-7+13x=0 |

Equations solver categories